Low-Power Resistive Switching Characteristic in HfO(2)/TiO(x) Bi-Layer Resistive Random-Access Memory - Ding, Xiangxiang (Nanoscale Res Lett, 2019)
Resistive random-access memory devices with atomic layer deposition HfO(2) and radio frequency sputtering TiO(x) as resistive switching layers were fabricated successfully. Low-power characteristic with 1.52 μW set power (1 μA@1.52 V) and 1.12 μW reset power (1 μA@1.12 V) was obtained in the HfO(2)/TiO(x) resistive random-access memory (RRAM) devices by controlling the oxygen content of the TiO(x) layer. Besides, the influence of oxygen content during the TiO(x) sputtering process on the resistive switching properties would be discussed in detail. The investigations indicated that “soft breakdown” occurred easily during the electrical forming/set process in the HfO(2)/TiO(x) RRAM devices with high oxygen content of the TiO(x) layer, resulting in high resistive switching power. Low-power characteristic was obtained in HfO(2)/TiO(x) RRAM devices with appropriately high oxygen vacancy density of TiO(x) layer, suggesting that the appropriate oxygen vacancy density in the TiO(x) layer could avoid “soft breakdown” through the whole dielectric layers during forming/set process, thus limiting the current flowing through the RRAM device and decreasing operating power consumption.